Validity and factorial invariance of the general well-being index (Who-5 wbi) in peruvian university students - Caycho-Rodríguez, Tomás (2020)
Introduction: Owing to its importance in the development and evaluation of health policies in favor of the general population, there is currently a greater interest in the study of well-being. Therefore, a valid and reliable measurement of well-being is necessary. In this context, this study evaluated the evidence of validity based on the internal structure, reliability, and factor invariance by sex of the General Well- Being Index (who-5 wbi). Materials and Methods: A total of 499 university students (female = 271; male = 228) from the city of Trujillo, Peru, participated in the study. A confirmatory factor analysis, reliability by internal consistency, and factor invariance by sex were performed using a multigroup analysis. Results: The confirmatory factor analysis indicated that the 5-dimensional model with 5 correlated errors of items 1 and 4 presented a good fit (χ2 = 9.667 [gl = 4], p > 0.05; χ2/gl = 2.416; cfi = 0.994; rmsea = 0.053 [ic90% 0.006–0.097]; srmr = 0.018). In addition, acceptable reliability (ω = 0.758) and factor invariance by sex were reported. Conclusion: The who-5 wbi demonstrated empirical evidence in favor of validity based on internal structure, reliability of scores, and factor invariance that allow for a useful and rapid instrument for measuring subjective well-being in university students.